Affirmative Policy on the Recruitment of Civil Service Candidates with Disabilities: A Review of the Six Elements of Social Policy and the Capability Approach - Yulia Putri Puspitasari; Ida Widianingsih; Riswanda Riswanda (Eduvest - Journal of Universal Studies, 2026)
This study examines the affirmative policy for the recruitment of State Civil Apparatus Candidates (CASN) with disabilities in Tangerang City, Indonesia. The background of this research is the persistent employment inequality experienced by persons with disabilities despite the existence of national regulations mandating equal employment opportunities and disability quotas in government institutions. The study aims to analyze the design and implementation of the affirmative recruitment policy using Chambers and Bonk’s six elements of social policy and the Sen–Nussbaum capability approach. This research employed a qualitative case study method focusing on CASN recruitment periods in 2019, 2021, and 2023. Data were collected through in-depth interviews with government officials, civil servants with disabilities, and disability community representatives, as well as observation and document analysis. The findings show that the policy has successfully provided formal employment access through special quotas, lower examination thresholds, and accessible recruitment services. However, several limitations remain, including inadequate policy socialization, limited workplace accommodation, inaccessible information systems, and the persistence of social stigma in the work environment. These conditions narrow several capabilities of employees with disabilities, particularly bodily integrity and affiliation. The study concludes that affirmative recruitment policy should not only focus on quota fulfilment but also ensure inclusive workplace systems that expand the substantive freedom, dignity, and capabilities of persons with disabilities.